Knowledge, Attitude toward Screening and Prevention of Cervical Cancer among Women at HCT in UAE - Meskiri, Aisha; Musallam, Lama; Alkatheeri, Anfal; Almessabi, Naof (Global Journal of Health Sciences, 2024)
Purpose: Cervical cancer is one of the leading causes of death in the United Arab Emirates (UAE) among females. Knowledge and awareness toward cervical cancer has been proven to be essential toward decreasing the number of cervical cancer cases. In fact, adequate knowledge towards cervical cancer screening will help in early diagnosis and good prognosis outcome towards cervical cancer. The aim of this capstone project was to address the knowledge, attitude toward screening and prevention of cervical cancer among women at HCT in the UAE. Methodology: A quantitative cross-sectional study was conducted using an online survey that contained 22 multiple choice questions and was distributed via email. The sample size of this study is to target approximately 250-300 respondents and random sampling is used to select the participants. The data downloaded from Microsoft Forms into a Microsoft Excel sheet (version 16.36). To analyze the data, SPSS version 25.0 was used and the frequency, percentage tables were constructed for each section of the survey. Results: Responses of 196 participants were used in the data analysis. The vast majority of the participants (55.1%) were aged between 21- 25 years old and were mainly from Abu Dhabi campus (91.8%). A significant association was observed between the field of education and the knowledge of cervical cancer (p=0.002, p˂0.05). Additionally, screening knowledge and attitude toward cervical cancer were also noted to have an association between age (p=0.022, p˂0.05) and field of education (p=0.002, p˂0.05). Cervical cancer prevention had a strong association between age (p=0.007, p˂0.05), nationality (p=0.004, p˂0.05), and field of education (p=0.000, p˂0.05). Furthermore, 54.08% of participants had average knowledge and attitude toward screening and prevention of cervical cancer. Unique Contribution to Theory, Practice and Policy: Despite the strong association between field of education and the overall knowledge toward cervical cancer. Awareness sessions conducted by wide sponsors such as students’ life, campus operation, and department of health, will help in increasing cervical cancer knowledge and attitude. Based on the findings, it is recommending exploring female’s perspective in the UAE towards receiving HPV self-sampling kit at home, which helps to identify HPV positive females, therefore estimating the chances of developing cervical cancer.